IMPROVING THE EFFICIENCY OF HYDRAULIC ENGINEERING SYSTEMS BASED ON GEOGRAPHICAL INFORMATION SYSTEMS - Laylo Butt; Yarbekov Mansur Sobirovich; Alisherov Isobek Botir o'g'li; Narzullayeva Nilufar Lutfullo qizi (TADQIQOTLAR, 2026)
Abstract: Hydraulic engineering systems have always played a critical role in supporting the development of human civilization by controlling, storing, and distributing water for diverse requirements such as agriculture, municipal needs, industrial processes, and environmental sustainability. Over time, the complexity and scope of hydraulic infrastructure have expanded dramatically. Dams, reservoirs, irrigation networks, drainage systems, canals, weirs, and soil retention structures all exist to manage the distribution and behavior of water in both natural and artificial landscapes.